1998
DOI: 10.1191/096032798678907937
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aggression, sexual behavior and fertility in adult male rat following long-term ingestion of four industrial metals salts

Abstract: 1. The effect of long-term ingestion of the industrial metals salts, manganese sulfate, aluminum chloride, lead acetate and copper chloride was investigated on aggression, sexual behavior and fertility in male rat. Adult male rats ingested solutions of these salts along with drinking water at a concentration of 1000 p.p.m. for 12 weeks. 2. Male rat sexual behavior was suppressed after the ingestion of manganese sulfate, aluminum chloride, lead acetate and copper chloride. The ingestion of solutions of these sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 0 publications
6
18
0
Order By: Relevance
“…The histopathological alterations induced in the testis of As 2 O 3 treated mice involves distortion of seminiferous tubules with partial to almost complete disintegration of connective tissue between them; loss of lumen in the tubules due to desquamation and distortion of germinal epithelial and other tubular cells and cytoplasmic vacuolization in spermatogonia and spermatocytes which are more pronounced in 96 hours post-treatment mice. These results are in agreement with the data published by Parizek (1960), Mason et al (1964), Favino et al (1966), Saksena and Lau (1979), Sharma et al (1980), Elbetieha and Al-hamood (1997), Bataineh et al (1998), Mayyas et al (2005) and Yang et al (2006) for many other heavy metals. In the present study a significant reduction in sperm amount (some seminiferous tubules are totally devoid of sperm) was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The histopathological alterations induced in the testis of As 2 O 3 treated mice involves distortion of seminiferous tubules with partial to almost complete disintegration of connective tissue between them; loss of lumen in the tubules due to desquamation and distortion of germinal epithelial and other tubular cells and cytoplasmic vacuolization in spermatogonia and spermatocytes which are more pronounced in 96 hours post-treatment mice. These results are in agreement with the data published by Parizek (1960), Mason et al (1964), Favino et al (1966), Saksena and Lau (1979), Sharma et al (1980), Elbetieha and Al-hamood (1997), Bataineh et al (1998), Mayyas et al (2005) and Yang et al (2006) for many other heavy metals. In the present study a significant reduction in sperm amount (some seminiferous tubules are totally devoid of sperm) was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The present study is probably first of its kind. Similar effects of heavy metals on the tissues of testis, liver and kidney have been reported by Saksena and Lau (1979), Bataineh et al (1998), and Mayyas et al (2005) in testis; Karmaker et al (2000) in liver and Garba et al (2007) in renal organs. Mechanism for the cytoplasmic vacuolization has been given by Robbins and Angell (1976) as one of the important responses to all forms of cell injury.…”
Section: Discussionsupporting
confidence: 64%
“…Few of these studies are on mammalian tissues. The histopathological alterations induced by different heavy metals in the tissues of testis, liver and renal organs have been reported by Elbetieha and Al-hamood (1977), Sharma et al (1980), Kwon et al (1997), Bataineh et al (1998), Mayyas et al(2005), Yang et al (2006) and Garba et al (2007). There have been no reports on the alteration of histoarchitecture in the gut of animals in response to heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, AlCl 3 exposure can lead to testicular injuries, especially as a result of increased oxidative stress [25][26][27][28] . Exley [29] and Yousef et al [25] have reported that aluminum exerts a pro-oxidant activity and promotes oxidation both in vitro and in vivo. Additionally, in rabbits, AlCl 3 can induce free radical generation and inhibit antioxidant enzymes and other components of the antioxidant system in a variety of organs including the liver, testis, kidney, lung and brain [30] .…”
Section: Introductionmentioning
confidence: 99%